Republished: Trigeminocardiac reflex caused by selective angiography of the middle meningeal artery. (14th July 2016) - Tamura, Takamitsu; Rex, David E; Marosfoi, Miklos G; Puri, Ajit S; Gounis, Matthew J; Wakhloo, Ajay K
Abstract : We describe an interesting case of trigeminocardiac reflex (TCR) caused by selective angiography of the middle meningeal artery (MMA). A 28-year-old woman presented with a symptomatic meningioma. Preoperative tumour embolisation was performed. In the procedure, when selective MMA angiography was done with Omnipaque 300 mg I/mL for 3 mL by manual injection, the patient complained of flashing lights in her eye followed by vomiting and bradycardia down to 40 bpm without increased intracranial pressure signs. On selective MMA angiography, the choroidal crescent and arteries of the periorbital region were opacified by anastomosis from the MMA via the meningo-ophthalmic artery. We diagnosed that her symptoms were caused by selective MMA angiography leading to high pressure stimulation towards the ophthalmic nerve innervation around the orbit as a TCR. We suggest that the operator should be prepared to manage TCR during treatment with expected selective MMA angiography, and gentle low pressure contrast injection should be attempted.